Heterogeneity of Treatment Effects of Laser Epilation on Pilonidal Disease Recurrence: A Randomized Clinical Trial - Katherine C. Bergus, MD, MPH; Carley Lutz, BS; Jennifer Cooper, PhD; Lindsey Asti, PhD, MPH; Lindsay Gil, MD, MPH; Cory Criss, MD; Katherine J. Deans, MD, MHSc; Peter C. Minneci, MD, MHSc (Annals of Surgery Open)
Objective:. To investigate the heterogeneity of treatment effects (HTE) of laser epilation in preventing pilonidal disease recurrence through analysis of prespecified clinical factors. Background:. Pilonidal disease is a common, painful disease affecting 1% of the population aged 15 to 30 years with postoperative recurrence rates as high as 30% to 40%. Methods:. Single-institution randomized controlled trial from September 2017 to September 2022 with 1-year follow-up, including patients aged 11 to 21 years with pilonidal disease undergoing gluteal cleft laser epilation and standard care (improved hygiene and mechanical or chemical depilation) or standard care alone. Results:. In total, 302 patients were enrolled with 151 randomized to each intervention. 1-year follow-up was available for 96 patients in the laser group and 134 in the standard care group. There were no significant differences in treatment effects based on sex, body mass index, previous disease, prior surgical excision, or annual household income (all P > 0.05). HTE was identified by race and ethnicity (P = 0.005) and health insurance type (P = 0.001). Recurrence among non-Hispanic white patients was 4% (3/75) with laser treatment and 31.6% (31/98) with standard care versus 38.9% (7/18) with laser treatment and 38.2% (13/34) with standard care among all other racial/ethnic groups. Recurrence rates among privately insured patients were 4.0% (3/75) with laser treatment and 33.3% (29/87) with standard care versus 36.8% (7/19) with laser treatment and 29.7% (11/37) with standard care in patients with public insurance. Conclusions:. The effectiveness of laser epilation to reduce pilonidal disease recurrence rates may vary based on race and ethnicity and insurance type. Additional studies are warranted to investigate this potential HTE.